Modern Environmental Perspectives, and Environmentalism including issues of Sustainability (International Journal of Food and Nutritional Sciences, 2022)
Environmentalism is a comprehensive philosophical, ideological, as well as social movements dedicated to the preservation and wellbeing of the natural world as well as natural resources. It may be accomplished via a procedure of collective awareness mobilization and public engagement in environmental concerns and problems. It envisions the concept and practice of protecting our ecology as socio-ecological feelings. Rapid population expansion, boundless consumption, as well as optimal exploitation of nature as well as natural resources have reconfigured the notion of sustainability in today's hyper-industrial society. The three foundations of modern environmental sustainability are society, economics, and the environment. Environmental sustainability and its practical applications are very beneficial in forming responsible judgments and strategies that will limit our negative environmental impact. It's not just about lowering the amount of garbage we make or consuming less energy; it's about making the most of our natural resources while also considering future demands. Environmental sustainability is now a research topic that is receiving a lot of attention from the media, as well as various government agencies, policymakers, and sociologists. The goal of this research is to determine the impact of new perspectives and debates on environmental protection, as well as the resulting issues in the utilization of nature and natural resources. The future prospectus of this paper is to comprehend contemporary environmental viewpoints and the developing concerns of sustainability in modern socio-ecological contexts.